Preventive Effect of Flavonoid Extract from the Peel of Gonggan (Citrus reticulata Blanco Var. Gonggan) on CCl4-Induced Acute Liver Injury in Mice - Wu Y; He Y; Wang R; Zhao X (Dove Medical Press, 2021)
Ya Wu,1,2,* Yongpeng He,3,4,* Rui Wang,1,2 Xin Zhao1 1Chongqing Collaborative Innovation Center for Functional Food, Chongqing Engineering Research Center of Functional Food, Chongqing Engineering Laboratory for Research and Development of Functional Food, Chongqing University of Education, Chongqing, 400067, People's Republic of China; 2College of Biological and Chemical Engineering, Chongqing University of Education, Chongqing, 400067, People's Republic of China; 3Chongqing Key Laboratory of Translational Research for Cancer Metastasis and Individualized Treatment, Chongqing University Cancer Hospital & Chongqing Cancer Institute & Chongqing Cancer Hospital, Chongqing, 400030, People's Republic of China; 4Department of Biochemistry and Molecular Biology, College of Basic Medical Sciences, Southwest Medical University, Luzhou, 646000, People's Republic of China*These authors contributed equally to this workCorrespondence: Xin Zhao Tel/Fax +86-23-62653650Email zhaoxin@cque.edu.cnObjective: Citrus peel, a waste product of citrus consumption and processing, is rich in flavonoids. This study aimed to study the protective effect of flavonoid extract from the peel of gonggan (Citrus reticulata Blanco var. gonggan) on acute chemical liver injury.Materials and Methods: We established a chemical liver injury model induced by carbon tetrachloride (CCl4) in mice. The flavonoid composition in gonggan (Citrus reticulata Blanco var. gonggan) peel was detected by HPLC. The histopathological sections of liver, related biochemical indicators in serum and liver, and related genes were examined to evaluate the protective effect of gonggan peel flavonoid extract (GPFE).Results: The results showed that GPFE contained narirutin, hesperidin, nobiletin, tangeretin, and 5-demethylnobiletin. After 14 days of intragastric administration of GPFE, the result showed GPFE could reduce the increase in liver index, serum alanine aminotransferase (ALT), and aspartate transaminase (AST) levels caused by CCl4. At the same time, pathological sections of liver confirmed that GPFE alleviated the damage to liver tissue. Moreover, biochemical indicator results showed that GPFE increased the activities of superoxide dismutase (SOD) and catalase (CAT) in liver tissue and reduced the content of malondialdehyde (MDA). Also, it reduced the levels of inflammation factors: tumor necrosis factor-α (TNF-α), interferon-γ (IFN-γ), interleukin (IL)-1β, and IL-6. In addition, q-PCR results showed that GPFE upregulated mRNA expression levels of nuclear factor erythroid 2-related factor 2 (Nrf2), copper/zinc superoxide dismutase (SOD1), manganese superoxide dismutase (SOD2), glutathione peroxidase (GSH-Px), γ-glutamylcysteine synthetase (γ-GCS), CAT, and downregulated IL-6 and TNF-α mRNA expression levels. The mechanism of GPFE may be related to the inhibition of oxidative stress and inflammation.Conclusion: The experiment indicates GPFE has a good protective effect on acute chemical liver injury in mice induced by CCl4 via antioxidant and anti-inflammatory pathways.Keywords: anti-inflammation, anti-oxidative, citrus peel, liver injury